Alleviating a Nomad's Anguish: Successful Treatment of a Case of Leg Mycetoma—A Case Report. (3rd December 2012) - Maina, Anthony Muchiri; Macharia, Joseph Theuri
Abstract : Introduction . Mycetoma is a localized, chronic, progressive, granulomatous, inflammatory, non contagious, tumour-like lesion with sinuses discharging different types of granules. The organisms are usually inoculated into any body part subject to trauma-usually the foot. Treatment is medical and/or surgical. Prognosis is good in early cases with high recurrences in late cases or those inadequately treated. The authors describe the successful treatment of a severe case of leg mycetoma, with combined surgical and medical therapies.